2019
DOI: 10.1002/ppul.24358
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of nasal mask‐delivered HFOV in neonates: A physiologic study

Abstract: Objectives To clarify if nasal mask influences noninvasive high‐frequency oscillatory ventilation (NHFOV) mechanics to optimize the clinical use of nasal mask‐delivered NHFOV. Working Hypothesis Nasal mask may affect the mechanical efficacy of NHFOV. Methodology We designed a physiologic study composed of an in vitro phase aiming to investigate pressure transmission and volume delivery in a bench model of nasal mask‐delivered NHFOV. In a second phase, we measured the leaks in vivo in a series of neonates recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These may impact on the efficacy of NIPPV as some of them were suboptimal. Moreover, the use of such different interfaces cannot reduce the leak and improve pressure transmission while the mouth is open, even if NIPPV is used [27]. We have used a low threshold of 30% FiO2 for indication of surfactant therapy instead of a higher one which may have some bearing on the results.…”
Section: Discussionmentioning
confidence: 99%
“…These may impact on the efficacy of NIPPV as some of them were suboptimal. Moreover, the use of such different interfaces cannot reduce the leak and improve pressure transmission while the mouth is open, even if NIPPV is used [27]. We have used a low threshold of 30% FiO2 for indication of surfactant therapy instead of a higher one which may have some bearing on the results.…”
Section: Discussionmentioning
confidence: 99%
“…However none of the previous studies have used both simulatenously. Mask delivered nHFOV has more dampening effect, therefore theoretically would require more aggressive ventilatory parameters [10]. In our case, cycling of the interfaces were done for comfort of the babies and whether it caused a drop in e cacy of nHFOV cannot be ascertained.…”
Section: Discussionmentioning
confidence: 93%
“…This could have low the requirements of IMV in the research groups. Non-invasive ventilation, which has previously been indicated as being preferred for premature neonates undergoing MIST, can be used to counteract the negative effects of MIST linked to limited air flow and airway resistance (10) . Even in physiological research, NIPPV has been demonstrated to be effective in preventing leaks and tracheal blockage caused by MIST catheterization (5) .…”
Section: Discussionmentioning
confidence: 99%